Terminasi Diskursus Poros Maritim Dunia dalam Kebijakan Luar Negeri Presiden Joko Widodo - Pramudia, Putu Shangrina (FOCUS, 2025)
This study explores the termination of the Global Maritime Fulcrum (GMF) discourse in President Joko Widodo’s foreign policy. Initially central to his 2014 presidential campaign and early administration, the GMF concept—with its five foundational pillars—was envisioned to transform Indonesia into a maritime-oriented nation, revive its maritime identity, and enhance its role in Indo-Pacific geopolitics. However, as Jokowi’s first term ended, the GMF gradually lost prominence. It was no longer promoted during the 2019 campaign nor prioritized in his second-term foreign policy agenda. Using the frameworks of national role conception, role contestation, and role legitimacy, this paper argues that despite Indonesia's alignment with regional geopolitical dynamics and minimal vertical or systemic contestation, the GMF discourse declined due to Jokowi’s failure to secure horizontal legitimacy among domestic political elites. These internal political constraints ultimately hindered the implementation and legitimacy of the GMF, rendering it irrelevant to Indonesia’s foreign policy during Jokowi’s second term.